Penghindaran Pajak dan Strategi Perusahaan - Audia Salsabila, Revika; Puspa Midiastuty, Pratana; Suranta, Eddy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Through the use of prospector tactics versus defender actions, this study seeks to show the many ways that companies engage in tax avoidance. This study uses proxies such as Effective Tax Rate (ETR) and Book Tax Difference (BTD) to examine tax avoidance behavior. The typology developed by Miles and Snow (1978) is used to define the prospector and defender methods. Within the scope of this study, agency theory is used to establish the relationship between the prospector approach and corporate defense practices and tax avoidance carried out by the corporate sector. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX), and the research period 2017-2022 is the time period considered. To select the sample for this investigation, purposive sampling was used. There were 105 companies and 630 observations included in the sample selection procedure. For the purpose of evaluating each hypothesis, we used two separate sampling methods. The test findings show that while there is no difference in tax avoidance activities among firms using the book tax difference (BTD) proxy, there is variation in tax avoidance actions among firms using prospector tactics and defenses in terms of the efficacy of Effective Tax Rate (ETR). Adopt a strategy that is defensive and prospective.